Penggunaan Media Audio Visual Berbasis YouTube untuk Meningkatkan Minat Belajar Daring Siswa pada Mata Pelajaran Fiqih: Studi pada Bab Kaidah Amar dan Nahi - Saini, Mukhamat; Fauzi, Muhammad Umar; Sujoko, Sujoko (IERA, Islamic Education and Research Academy, 2020)
This study aims to improve students' online learning interest in the subject of Fiqh on the topic of Kaidah Amar and Nahi in class XII-MIA MA Al Khidmah Ngronggot in the academic year 2020/2021 through the use of YouTube-based audiovisual media. The research method used was classroom action research with two cycles and four stages: planning, action, observation, and reflection. The research subjects were 30 students of class XII-MIA MA Al Khidmah Ngronggot. Data were collected through tests and learning interest questionnaires and analyzed using qualitative and quantitative descriptive analysis techniques. The results showed that the use of YouTube-based audiovisual media is effective in improving students' online learning interest in the subject of Fiqh on the topic of Kaidah Amar and Nahi in class XII-MIA MA Al Khidmah Ngronggot in the academic year 2020/2021. In Cycle I, there was a 26.67% increase in learning interest with a percentage of student learning mastery of 70%. Meanwhile, in Cycle II, there was a 23.33% increase in learning interest with a percentage of student learning mastery of 86.67%. These results indicate that the use of YouTube-based audiovisual media is effective in improving students' online learning interest in the subject of Fiqh on the topic of Kaidah Amar and Nahi in class XII-MIA MA Al Khidmah Ngronggot in the academic year 2020/2021. Therefore, it is recommended that teachers use YouTube-based audiovisual media in online learning to improve students' learning interest.